2013
DOI: 10.1016/j.neurobiolaging.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment restores neurogenesis and rapid acquisition in aged rats

Abstract: Strategies combatting cognitive decline among the growing aging population are vital. We tested whether environmental enrichment could reverse age-impaired rapid spatial search strategy acquisition concomitantly with hippocampal neurogenesis in rats. Young (5–8 mo) and aged (20–22 mo) male Fischer 344 rats were pair-housed and exposed to environmental enrichment (n=7 young, 9 aged) or housed individually (n=7 young, 7 aged) for ten weeks. After five weeks, hidden platform trials (5 blocks of 3 trials; 15m IBI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 77 publications
8
121
3
2
Order By: Relevance
“…Rodent studies in which social, motor, cognitive and physical stimulation is provided have revealed that environmental enrichment (EE) in aged rats improves the spatial memory performance, increasing the ability to rapidly acquire a spatial memory task, along with a flexible use of spatial information (Baraldi et al, 2013;Harati et al, 2011;Speisman et al, 2013). Also, EE, in contrast to standard housing conditions, produces better indices of emotionality and faster adaptation to novel situations (Larsson et al, 2002;Zimmerman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent studies in which social, motor, cognitive and physical stimulation is provided have revealed that environmental enrichment (EE) in aged rats improves the spatial memory performance, increasing the ability to rapidly acquire a spatial memory task, along with a flexible use of spatial information (Baraldi et al, 2013;Harati et al, 2011;Speisman et al, 2013). Also, EE, in contrast to standard housing conditions, produces better indices of emotionality and faster adaptation to novel situations (Larsson et al, 2002;Zimmerman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the Aged EE group animals had brain mass greater than CG animals. In a recent study, Speisman and colleagues (2013) found that the maintenance of aged rats in an enriched cage contributes to improve the cognitive responses in cognitive tests and this occurs as an adaptation to neogenesis promoted by EE (SPEISMAN et al , 2013). Another recent study, comparing the effects of EE in adult and aged animals concluded that this type of housing contributes to promoting improvements in cognitive test response, although it promotes brain changes in different regions (MENDES et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Aussi, l'EE ne renverse pas les effets du vieillissement sur la différentiation neurale. La majorité des nouvelles cellules expriment un phénotype neuronal et en minorité un phénotype gliale [29]. Les études comparants rongeurs âgés et modèles de la MA confirment la baisse accrue du renouvellement cellulaire des populations malades [30].…”
Section: Environnement Enrichi Et Neuroplasticitéunclassified